Energy and exergy analysis of a rotary kiln used for plaster production - Gurturk, Mert; Öztop, Hakan Fehmi (Pergamon-Elsevier Science Ltd, 2014)
This paper presents, the energy and exergy analysis of a rotary kiln used for plaster production was performed. Some parameters, such as losses, irreversibility and design were used for determining the energy and exergy efficiencies. Capacity of the rotary kiln is 22 ton/h and the power of it is 7.8 MW. Based on the calculations from the measured values of the rotary kiln, the energy and exergy efficiencies are calculated as 69% and 16%, respectively. The exergy analysis showed that the exergy destruction rate is determined to be 2969.97 kW which corresponds to 66% of the total exergy input. Also, considering governing parameters, some suggestions and discussions are carried out to get better working conditions and increasing the energy and exergy efficiencies of the rotary kiln. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Exergy; Energy; Rotary kiln; Plaster; Gypsum